2017
DOI: 10.1007/s11255-017-1573-3
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in maintenance hemodialysis patients: an epidemiologic survey in Hefei

Abstract: Our findings demonstrated that the prevalence of RLS was 14.5% in Hefei. High hemoglobin level was a protective factor for RLS, and high alkaline phosphatase was an independent risk factor. RLS affects many aspects of quality of life and sleep quality, which may contribute to the presence of depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Patients with RLS often experience various discomforts such as limb pain, swelling, burning, creeping sensation, which can lead to difficulty falling asleep and sleep interruption. Patients with RLS may suffer daytime sleepiness, fatigue, inattention, and decreased interest, depression, irritability, and other anxiety and depression emotions, affecting the quality of sleep and quality of life of patients (2,(23)(24)(25). Vitamin D regulates the production of melatonin in the body and plays an important role in regulating the circadian rhythm of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RLS often experience various discomforts such as limb pain, swelling, burning, creeping sensation, which can lead to difficulty falling asleep and sleep interruption. Patients with RLS may suffer daytime sleepiness, fatigue, inattention, and decreased interest, depression, irritability, and other anxiety and depression emotions, affecting the quality of sleep and quality of life of patients (2,(23)(24)(25). Vitamin D regulates the production of melatonin in the body and plays an important role in regulating the circadian rhythm of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that depression affects various parts of sleep. Recent polysomnography studies by Lee et al have found an association between depression and insomnia [24], and an association between depression and restless legs syndrome has also been found in other studies [25][26][27]. Depression has been shown to be a risk factor for excessive daytime sleepiness [28,29].…”
Section: Discussionmentioning
confidence: 83%
“…As shown in Figure 6 , based on VOSviewer’s overlay visualization, keywords around restless legs syndrome, case reports, insomnia, functional capacity, and feasibility have been frequently mentioned in recent years. Based on this network mapping and the results of this systematic review, future research should focus on (1) The prevalence of restless legs syndrome is particularly prominent in hemodialysis patients, which is easily clinically neglected [ 69 ], and severely affects sleep and significantly reduces the quality of life of dialysis patients [ 70 ]. Currently, there is a lack of targeted drugs, and acupuncture seems to improve the severity of restless legs syndrome symptoms [ 71 ].…”
Section: Discussionmentioning
confidence: 99%